ANALISIS EKSPERIMENTAL GAYA DAN TEGANGAN MATERIAL KOMPOSIT PADA PERANCANGAN PELINDUNG DADA PENGENDARA SEPEDA MOTOR - Irvin .; M Sabri; Mahadi .; Bustami Syam; Syahrul Abda (Jurnal Dinamis, 2017)
The goal of this research is to identify the stress and force that occur in the motorbike body protector which created using composite material in order to protect human chest. Free-fall drop test is done using Multifunctional Free-fall impact test tools. Specimen placed to the test rig which has adjustable drop height. The fall time of test is calculated using 8 inductive proximity sensors. It will fall and crashed the anvil. Impact force that occurs by the drop is measured using a load cell that placed under the anvil. Measurement data will transfer to analog device that changed the analog signal into a digital signal. Result data is saved in the PC as a table of force (F) and time (t). Experimental test data for the body protector specimens using GFRP at the impactor height 3 m is 698.17 kgf and stress 0.014 MPa. After the result compared with the computational result the mean transmission impact force is 14.95 kN and the maximum transmission impact force is 29.18 kN. Thus the transmission force that occur is not pass the European de Normalization (EN 1621-2) which for average impact force transmitted is 20kN and maximum impact force transmitted is 35 kN.